Commons and tourism: an integrative review - Lacerda, Leonardo Lincoln Leite de; Biz, Alexandre Augusto (Anais Brasileiros de Estudos Turísticos, 2024)
The development of tourism on the national scene generally occurs through public initiative and/or public initiative. However, it is possible that there are other ways of managing the elements that make up the tourist activity to achieve a more balanced development between the parties involved, such as the initiative of organized civil society, which refers to the Commons Theory. Therefore, the general objective of this article was to analyze studies that addressed tourism and commons. And as a method used, an integrative review was carried out using the descriptors “commons” AND “tourism” in the Scopus, Web of Science and in SciELO databases. After survey and selection by quality criteria, twelve articles were analyzed. Among the results, it was observed: a) that the focus of the studies lies on the management of natural resources (common-pool resources) of the destination, showing an emphasis on second-generation Commons studies, based on Ostrom (1990); b) that the tragedy of the tourist commons is more related to the lack of Ostrom’s (1990) success principles 4 and 5, but also 1, 3, and 6; c) that the success of the tourist commons is more linked to principles 2, 3, 4, 5, 6; and d) knowledge management can be seen as a strengthener of the tourist commons, mainly for expanding the awareness of those involved in tourism and for knowledge transfer among such actors. The main contribution of the study is to show that managers of common resources (of various natures) in the tourism activity can use the eight success principles of a common-pool resource to guide sustainable tourism development, preferably aligning with the perspective of knowledge management, notably the knowledge commons, to increase the chances of success of the tourism common good.